STRATEGI DALAM MENANGANI KESEJAHTERAAN LANJUT USIA TERLANTAR (STUDI KASUS: UPTD. PELAYANAN SOSIAL LANJUT USIA BINJAI DINAS SOSIAL PROVINSI SUMATERA UTARA) - Silalahi, Denada; Nur Afifah (CV. Denasya Smart Publisher, 2025)
The welfare of neglected elderly individuals is a pressing social issue in Indonesia, particularly in regions where social protection systems remain limited. This issue has become a major concern in social services, especially within local government institutions. The Binjai Elderly Social Service Unit (UPTD Pelayanan Sosial Lanjut Usia Binjai) is one of the institutions responsible for providing protection and care for elderly individuals who are abandoned or have no family support. This study examines the strategies implemented by the Binjai Elderly Social Service Unit, which operates under the North Sumatra Provincial Social Service Office, in addressing the welfare of neglected elderly individuals. The analysis employs John M. Bryson’s (2008) strategic management framework, which consists of four key elements: input, strategic process, output, and outcome. Using a descriptive qualitative approach, the research was conducted through in depth interviews, direct observations, and documentation. The findings indicate that the UPTD provides essential services such as shelter, food, healthcare, and spiritual support. However, several challenges persist, including limited funding, a shortage of caregivers, and the absence of permanent medical personnel. Although the strategic process has been carried out according to plan, its effectiveness is constrained by these resource limitations. The results of this study are expected to provide valuable insights for policy development and the improvement of social service quality for neglected elderly individuals through enhanced financial support, better facilities, and increased human resources, ultimately fostering a sustainable elderly welfare strategy.